HUMVEES - Willis, John, 1989- (New York, NY : Lightbox Learning Inc., 2024)
"Did you know that the first Humvee was put into service more than 30 years ago? Before that, the U.S. military had trucks. Learn more about these large, powerful machines in Humvees, a Mega Military Machines book."--Back cover
"AV2 by Weigl."
Go to AV2 online catalog at www.openlightbox.com
Keywords: Hummer trucks -- Juvenile literature; Juvenile works